Half a Century of Technological Advances in Pulmonary Drug Delivery: A Personal Perspective - Clark, Andrew R. (Frontiers in Drug Delivery, 2022)
The last half century of pulmonary product development is reviewed in the context of the main drivers of innovation, technology developments and the advancement of the science. A perspective on development timeframes, patent lifetimes and the odds of success of developing of new inhaler technologies is presented.